Momo Arashima duels the queen of death - Sugiura, Misa (Sugiura, Misa. Momo Arashima, 2025)
"Momo Arashima is half goddess and half human--torn between two worlds. But with her friends Danny, Ryleigh, Jin, and Niko by her side, she's finally starting to find a place where she belongs. Too bad none of that matters when Izanami, the treacherous goddess of death, threatens the life of someone Momo loves and forces her into a terrible bargain.